OCHRONA SUI GENERIS BAZ DANYCH W PRAWIE POLSKIM - Sikorski, Rafał (Wydział Prawa i Administracji UAM, 2004)
The author presents here the Act on the Protection of Databases, adopted on June 27, 2001, which implements the European Community Directive on the legal protection of databases in the Polish law.
PROTECTION SUI GENERIS OF DATABASES IN THE POLISH LAW